The Effect of Education and Training (Diklat) and Self-fficacy on Employee Work Productivity With Work Engagement as A Mediating Variable at PT XYZ - Christina Tasya Sitorus; Riedel Paulus Jacobis (Lavish Opulent Education, 2026)
Empolyee work productivity is an important indicator in assessing organizational success, as it reflects the ability to generate outputs effectively and efficiently. In the face of changing dynamics, employee work productivity is influenced by various factors, such as education and training (diklat), self-efficacy, and work engagement.This study aims to analyze the effect of education and training (diklat) and self-efficacy on employee productivity, both directly and indirectly through work engagement as a mediating variable. The research was conducted on employees of PT XYZ, an oil and gas company, using a quantitative approach with a survey method. Data were collected through questionnaires and analyzed using SEM-PLS with SmartPLS. The results show that education and training (diklat) and self-efficacy has a positive effect on both employee work productivity and work engagement. In addition, work engagement has a positive effect on employee work productivity and mediates these relationships. These findings indicate that productivity improvement is influenced not only by competence but also by employee level of engagement in their work.